(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In our institute we have four hostels and all having their own individual mess, where daily a large amount of kitchen waste is obtained which can be utilized for better purposes. Biogas production requires Anaerobic digestion. Project was to create an Organic Processing Facility to create biogas which will be more cost effective, eco-friendly, cut down on land fill waste, generate a high-quality renewable fuel, and reduce carbon dioxide & methane emissions. Overall, by creating a biogas reactor on campus in the backyard of our hostels will be beneficial. Kitchen (food waste) was collected from different hostels of PACE IT & S Mess as feed stock for our reactor which works as an aerobic digester system to produce biogas energy. The anaerobic digestion of kitchen waste produces biogas, a valuable energy resource Anaerobic digestion is a microbial process for production of biogas, which consist of Primarily methane (CH4) & carbon dioxide (CO2). Biogas can be used as energy source and also for numerous purposes. But any possible applications require knowledge & information about the composition and quantity of constituents in the biogas produced. The continuously-fed digester requires addition of sodium hydroxide (NaOH) to maintain the alkalinity and pH to 7. For this reactor we have prepared our Inoculum than we installed batch reactors, to which inoculum of previous cow dung slurry along with the kitchen waste was added to develop our own Inoculum. A combination of these mixed inoculum was used for biogas production at 37°C in laboratory (small scale) reactor (20L capacity) In our study, the production of biogas and methane is done from the starch-rich and sugary material and is determined at laboratory scale using the simple digesters.